2009
DOI: 10.1111/j.1532-5415.2009.02242.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Significantly Influence Fall Risk in Community‐dwelling Elderly People in Japan

Abstract: patients with DLB have the highest Braak and Braak stages and would be classified as LBV from a clinico-pathological point of view. Although the main limit of this study was the lack of a pathological diagnosis, it reflects the common clinical situation. These results underscore the difficulty of a DLB diagnosis in the elderly population in which the prevalence of AD lesions is high and might alter the occurrence of clinical signs of DLB, 6 as well as the pattern of episodic memory impairment. Further research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
2
7
0
2
Order By: Relevance
“…Older age[15][16], female gender[16][17], and poorer visual acuity[18][19] were noted as risk factors for falling in previous studies. One study showed that falls were significantly associated with poor visual acuity and higher waist-to-hip ratio [19].…”
Section: Discussionmentioning
confidence: 77%
“…Older age[15][16], female gender[16][17], and poorer visual acuity[18][19] were noted as risk factors for falling in previous studies. One study showed that falls were significantly associated with poor visual acuity and higher waist-to-hip ratio [19].…”
Section: Discussionmentioning
confidence: 77%
“…The Working Group for Fall Prevention in the Japanese Ministry of Health, Welfare and Labor has developed a 21‐item Fall Risk Index (FRI) 2 for early detection of the risk of falls in elderly people. It has been found that fallers are older, more disabled, and more depressed and had higher scores on the FRI than nonfallers 3 and that FRI score was closely associated with aging and sex differences in community‐dwelling elderly persons in Japan 4 . Although the significance of the FRI has been demonstrated in cross‐sectional settings, the cutoff score for predicting falls in elderly people has not been established in longitudinal studies.…”
mentioning
confidence: 99%
“…Subjects who answered yes to the question were considered to be fallers, and those who answered no, not at all, were considered to be nonfallers. The FRI consists of 21 questionnaire‐based items identified through a search of international and Japanese research articles that surveyed the history of falls within a year on a yes/no basis 2,4,5 . The 21 items included in the FRI encompassed physical, cognitive, emotional, and social aspects of functioning and environmental factors.…”
mentioning
confidence: 99%
“…In our previous cross-sectional study, we found that fallers were older, more disabled, more depressed and had higher FRI-21 scores than non-fallers. 3 We also showed that FRI-21 score was closely associated with age and sex differences, 9 and that a cut-off of 9/10 was a useful predictor of falls in Japanese community-dwelling elderly. 10 History of falls is a known fall risk, 11 and falls themselves are closely correlated with dependence of BADL.…”
Section: Introductionmentioning
confidence: 73%